Pengembangan E-Modul Serli Berbasis Android Materi Magnet bagi Siswa Sekolah Dasar - Rahayu, Enny; Azizah, Azizah; Ratman, Ratman; Risma, Iga; Sitepu, Melyani Sari (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This research is based on the lack of learning media that can help students during Distance Learning. Learning Media developed in this study can be used and accessed anywhere and anytime to help students understand the material being taught. The Media that will be developed in the research will be in the form of applications that help teachers in delivering material and help students to understand more about the material being taught. This study focused on science subjects, especially magnetic materials for Grade VI students. E-module is a learning module that is packaged into electronic form to facilitate the learning process that is made systemically, and is an example of the benefits of technology in the field of Education. The development of this e-module uses discovery learning approach. In developing e-module Seroid Learning media based on Android on magnetic material for Grade VI elementary school students . Achievement in this development to test apalikasi developed is included in the category of valid and practical, with research development methods RnD (Research and Development) using Thiagarajan 4D model that Define, Design, Develop, and Disseminate. The development of the serli e-module application will be carried out in the sixth grade of Inpres 12 Baiya, elementary school by conducting a small trial of 6 students.